Strategic cyber defense : a multidisciplinary perspective - Gheorghe, Adrian V.; Tatar, Unal; Gokce, Yasir (NATO science for peace and security series. Information and communication security ;, 2017)
With the increased dependence on digital and internet technologies, cyber security has come to be regarded as a national security issue, and the number of countries with a published cyber security strategy continues to rise. But these national cyber security strategies often run the risk of failing to address all the cyber security requirements of the many institutions within a given country, and the complex nature of the stakeholders involved and the networks formed by them means that the problem requires an interdisciplinary approach.0This book presents papers from the NATO Advanced Research Workshop (ARW) entitled?A Framework for a Military Cyber Defense Strategy?, held in Norfolk, Virginia, USA, in April 2016. The workshop focused on key priority areas for cyber defense along with NATO?s cyber defense policy implementation and brought together experts with an eclectic mix of backgrounds and specialties from a group of NATO member states and partner countries. The participants considered not only the technical implications of cyber security efforts, but also the legal, strategic, educational and organizational aspects, and the book reflects this wide view of the field and its intricacies, highlighting the complexity of cyber security and the many challenges it presents.